Performance of concrete containing crumb rubber and steel fiber at high temperatures - Siti Nurul Nureda Mohamad Zukri, 1992-, author; Mariyana Aida Ab. Kadir, supervisor; Fakulti Kejuruteraan Awam (2015)
Project Paper (Sarjana Muda (Kejuruteraan Awam - Struktur))- Universiti Teknologi Malaysia, 2015